Assessing consistency in the aerobic co-composting of faecal sludge and food waste in a municipality in Ghana - Nartey, Eric Gbenatey; Sakrabani, R.; Tyrrel, S.; Cofie, Olufunke O. (Springer, 2023)
Background: A faecal sludge (FS) co-composting study assessed the extent of consistency in compost characteristics between and within batches. The study focused on the consistency of the co-composting process by measuring the variability of key parameters.